project-i(s)les. - Delafortie, Lieven; Gonzalez-Sancho, Eva; St. Michielsgebouw, Brussel (Brussel : vzw artquake, 2001)
Boudewijns, Jan ; de Bus, Steven ; De Clerck, Mario ; de Maeyer, Kathleen ; de Smet, Annelies ; de Wilde, Frederik ; Dumont, Johan ; Goossens, Inge ; Hermans, Leen ; Laute, Vincent ; et al.
project-i(s)les, St. Michielsgebouw, Brussel, 15 juni tot en met 2 juli 2001
kunstcatalogus